If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + 2 = 10 Reorder the terms: 2 + 8m = 10 Solving 2 + 8m = 10 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 8m = 10 + -2 Combine like terms: 2 + -2 = 0 0 + 8m = 10 + -2 8m = 10 + -2 Combine like terms: 10 + -2 = 8 8m = 8 Divide each side by '8'. m = 1 Simplifying m = 1
| Log^7(4x+7)=2 | | ln(sqrt(x))=9 | | 2x+15=83 | | 35=19m-4m+5 | | 7r+3=-11 | | 3a+5a-a+7=7 | | p=320-4q | | x-9x-22=0 | | (12x-3)-(4x-4)= | | 4x*8x^2=90 | | 7/4x+1/5x=19/10 | | 125/2x9/4 | | 4y=6x-10 | | p=320+-4q | | 19=1-5k-7 | | 7+7y=-10y+10 | | 6.5(x)(x)+7x-8.5=0 | | 3x=2y+5 | | 0.25p=80-q | | 9c+6=8c+4 | | 4ln(7x)=18 | | 3t=30-2t | | ln(x+2)=ln(x-4)+ln(3) | | 2x+1=6x^2 | | 2x^2-18x+105=0 | | 2xX=7 | | 30x^2=270 | | -16=-x^2+11x | | 1/6x=5 | | (4x+3i)+(-2-i)= | | 16=-x+11x | | (9x-3)(6x+8)=0 |